2017
DOI: 10.1016/j.amjcard.2017.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Age-Adjusted Co-morbidity Index on Survival of Patients With Heart Failure Implanted With Cardiac Resynchronization Therapy Devices

Abstract: Age is an adverse prognostic factor in patients with heart failure. We aimed to assess the impact of age and noncardiac co-morbidities in the outcome of patients undergoing cardiac resynchronization therapy (CRT), and determine which of these two factors is the most important predictor of survival. The study involved a single-center retrospective assessment of 697 consecutive CRT implants during a 12-year period. Patient co-morbidity profile was assessed using the Charlson Co-morbidity Index (CCI) and the Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The CCI and ACCI became increasingly popular in medical research studies between 2005 and 2010 because they can be calculated using health claims data for clinical, epidemiological, or costutility studies [12,13,19,22]. The CCI was originally designed to predict mortality or the costs associated with chronic diseases in patients and has been extended to evaluate outcome after heart failure treatment [17] or ICU treatment [23]. However, whether it can be used as a prognostic index for acute care after ECPR has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCI and ACCI became increasingly popular in medical research studies between 2005 and 2010 because they can be calculated using health claims data for clinical, epidemiological, or costutility studies [12,13,19,22]. The CCI was originally designed to predict mortality or the costs associated with chronic diseases in patients and has been extended to evaluate outcome after heart failure treatment [17] or ICU treatment [23]. However, whether it can be used as a prognostic index for acute care after ECPR has not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the Charlson comorbidity index (CCI) [10] and age-adjusted CCI (ACCI) [11] have been repeatedly validated for estimating the longitudinal prognosis associated with multiple pre-existing comorbidities [12,13]. The ACCI has also been validated [14] in clinical scenarios such as cancer [15,16], heart failure [17], infectious disease, emergency surgery [18], intensive care units (ICUs), and even cost-effectiveness analysis of health care systems [13,19]. We considered whether the ACCI could be used as a useful inclusion / exclusion criterion for patients with ECPR.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the Charlson comorbidity index (CCI) [ 10 ] and age-adjusted CCI (ACCI) [ 11 ] have been repeatedly validated for estimating the longitudinal prognosis associated with multiple pre-existing comorbidities [ 12 , 13 ]. The ACCI has also been validated [ 14 ] in clinical scenarios, such as cancer [ 15 , 16 ], heart failure [ 17 ], infectious disease, emergency surgery [ 18 ], intensive care units (ICUs), and even the cost-effectiveness analysis of health care systems [ 13 , 19 ]. We considered whether the ACCI could be used as a useful inclusion/exclusion criterion for patients with ECPR.…”
Section: Introductionmentioning
confidence: 99%
“…Bhavnani et al reported that the CCI is predictive of mortality within 1 year of initial ICD implantation. CCI score has also been shown to predict mortality in cardiac resynchronization therapy (CRT‐D) recipients . High CCI at the time of initial ICD implantation also predicts depression and poor physical health status .…”
Section: Discussionmentioning
confidence: 99%
“…CCI score has also been shown to predict mortality in cardiac resynchronization therapy (CRT-D) recipients. 20,21 High CCI at the time of initial ICD implantation also predicts depression and poor physical health status. 22 Importantly, in a combined analysis of four randomized trials of ICD implantation for primary prevention, the survival advantage conferred by ICD implantation was diminished in patients with ≥2 comorbidities compared to those with fewer comorbidities.…”
Section: Discussionmentioning
confidence: 99%